2006
DOI: 10.1186/1471-2350-7-85
|View full text |Cite
|
Sign up to set email alerts
|

β2-adrenergic receptor and UCP3 variants modulate the relationship between age and type 2 diabetes mellitus

Abstract: Background: It is widely accepted that Type 2 Diabetes Mellitus (T2DM) and other complex diseases are the product of complex interplay between genetic susceptibility and environmental causes. To cope with such a complexity, all the statistical and conceptual strategies available should be used. The working hypothesis of this study was that two wellknown T2DM risk factors could have diverse effect in individuals carrying different genotypes. In particular, our effort was to investigate if a well-defined group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
(47 reference statements)
1
23
1
1
Order By: Relevance
“…This seems counter-intuitive at first glance, given that the derived allele shows signatures of positive selection based on human-chimp-comparisons (Bochdanovits et al 2009), and given the various positive associations that have been found for the derived allele with autism (Cheslack-Postava et al 2007) and health-related phenotypes (Gjesing et al 2007;Pinelli et al 2006;Stanzione et al 2007). On second sight, however, such antagonistic effects are what should be expected for derived alleles that are still variable today, despite positive selection acting on them recurrently, since the human and chimpanzee lineages split 6-7 million years ago (Harris 2008).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This seems counter-intuitive at first glance, given that the derived allele shows signatures of positive selection based on human-chimp-comparisons (Bochdanovits et al 2009), and given the various positive associations that have been found for the derived allele with autism (Cheslack-Postava et al 2007) and health-related phenotypes (Gjesing et al 2007;Pinelli et al 2006;Stanzione et al 2007). On second sight, however, such antagonistic effects are what should be expected for derived alleles that are still variable today, despite positive selection acting on them recurrently, since the human and chimpanzee lineages split 6-7 million years ago (Harris 2008).…”
Section: Discussionmentioning
confidence: 92%
“…The ancestral G allele of the rs1042714 SNP has been associated with increased risk of ischemic stroke (Stanzione et al 2007), high systolic blood pressure (Gjesing et al 2007), and type-2 diabetes (Pinelli et al 2006, but see Gjesing et al 2007). However, all effects we reported here remained virtually unchanged after controlling for selfreported histories of these three conditions or of cardiovascular diseases (only 13 subjects (8%) had diabetes and six (3.7%) ever had a stroke in this generally healthy sample).…”
Section: Confounding Effects Of Health Historymentioning
confidence: 98%
“…Despite strong functional evidence for the relevance of these three SNPs, the results for association with type 2 diabetes show significant between-study variation. To obtain a more definitive conclusion, we conducted a metaanalysis of 17 published articles with 28 outcomes from populations of different ethnic origins [11,13,14,19,[26][27][28][29][30][31][32][33][34][35][36][37][38]. We believe such a meta-analysis has a much greater possibility of reaching reasonably strong conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4, significant heterogeneity was observed among studies of the UCP2 −866G/A and Ala55Val polymorphisms in the overall populations, but no heterogeneity was found in the inherited models for the UCP3 −55C/T polymorphism. To investigate this further, the following covariates were considered: publication year, sex (ratio of males in cases Asian Sasahara et al [14] Ji et al [27] Hsu et al [30] Lee et al [31] Heidari et al [33] Vimaleswaran et al [35] Subtotal (I 2 =0.0%, p=0.562) European Wang et al [26] D'Adamo et al [13] Bulotta et al [28] Pinelli et al [29] Hsu et al [30] Hsu et al [30] Beitelshees et al [32] Voight et al [34] Subtotal (I 2 =38.0%, p=0.127) Cho et al [37] Hsu et al [30] Lee et al [31] Vimaleswaran et al [35] Subtotal (I 2 = 23.7%, p=0.264)…”
Section: Characteristics Of Studymentioning
confidence: 99%
See 1 more Smart Citation